Drug Discovery on Natural Products: From Ion Channels to nAChRs, from Nature to Libraries, from Analytics to Assays. (March 2019) - Otvos, Reka A.; Still, Kristina B. M.; Somsen, Govert W.; Smit, August B.; Kool, Jeroen
Natural extracts are complex mixtures that may be rich in useful bioactive compounds and therefore are attractive sources for new leads in drug discovery. This review describes drug discovery from natural products and in explaining this process puts the focus on ion-channel drug discovery. In particular, the identification of bioactives from natural products targeting nicotinic acetylcholine receptors (nAChRs) and serotonin type 3 receptors (5-HT3 Rs) is discussed. The review is divided into three parts: "Targets, " "Sources, " and "Approaches." The "Targets" part will discuss the importance of ion-channel drug targets in general, and the α7-nAChR and 5-HT3 Rs in particular. The "Sources" part will discuss the relevance for drug discovery of finding bioactive compounds from various natural sources such as venoms and plant extracts. The "Approaches" part will give an overview of classical and new analytical approaches that are used for the identification of new bioactive compounds with the focus on targeting ion channels. In addition, a selected overview is given of traditional venom-based drug discovery approaches and of diverse hyphenated analytical systems used for screening complex bioactive mixtures including venoms.